2014
DOI: 10.1038/nrneph.2014.91
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition receptors and the inflammasome in kidney disease

Abstract: Toll-like receptors (TLRs) and nucleotide-binding oligomerization domain receptors (NLRs) are families of pattern recognition receptors that, together with inflammasomes, sense and respond to highly conserved pathogen motifs and endogenous molecules released upon cell damage or stress. Evidence suggests that TLRs, NLRs and the NACHT, LRR and PYD domains-containing protein 3 (NLRP3) inflammasome have important roles in kidney diseases through regulation of inflammatory and tissue-repair responses to infection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
131
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(134 citation statements)
references
References 186 publications
2
131
0
1
Order By: Relevance
“…The regulation of TLR2 and TLR4 has been implicated in the pathogenesis of various kidney diseases, including urinary tract infection, AKI, kidney transplantation, and glomerulonephritis 8 . Emerging evidence has demonstrated the pivotal roles of TLR2 and TLR4 in the perpetuation of inflammation in diabetic nephropathy 132 .…”
Section: [H2] Involvement Of Tlrsmentioning
confidence: 99%
See 2 more Smart Citations
“…The regulation of TLR2 and TLR4 has been implicated in the pathogenesis of various kidney diseases, including urinary tract infection, AKI, kidney transplantation, and glomerulonephritis 8 . Emerging evidence has demonstrated the pivotal roles of TLR2 and TLR4 in the perpetuation of inflammation in diabetic nephropathy 132 .…”
Section: [H2] Involvement Of Tlrsmentioning
confidence: 99%
“…DAMPs are derived from damaged or dying cells, and include small molecules (ATP and DNA), particles (uric acid crystals and exogenous noxious factors such as asbestos) and environmental insults such as UV irradiation 7 . Systemic and local low-grade inflammation and release of proinflammatory cytokines are implicated in the pathogenesis of T1DM and T2DM.Furthermore, among the vascular complications of diabetes mellitus, subclinical inflammation is also known to contribute to the pathogenesis of diabetic nephropathy 4,8,9 . In this Review we provide an update on the functional roles of Toll-like receptors (TLRs) and NOD-like receptors (NLRs) in the pathogenesis of T1DM and T2DM, and its vascular complications, namely diabetic nephropathy 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is independent of the cause of kidney injury and can be detected in acute kidney failure and chronic kidney allograft nephropathy, autoimmune diseases like lupus nephritis or granulomatosis with polyangiitis, and even diabetic nephropathy. Chronic inflammation does not seem to be triggered by pathogens be it viruses, bacteria, or bacterial products (Leemans et al 2014).…”
mentioning
confidence: 99%
“…During the last few years, numerous endogenous ligands have been identified that can bind to damage-associated molecular patterns (DAMPs) and trigger inflammation by activating nuclear factor kappa b and secreting cytokines and chemokines (Leemans et al 2014). The resulting kidney tissue damage is associated with the release of more endogenous ligands and, therefore, ends in a self-sustaining vicious circle.…”
mentioning
confidence: 99%